Suddenly Telework: Job Crafting as a Way to Promote Employee Well-Being? - Stempel, Christiane R.; Siestrup, Katja (Frontiers in Psychology, 2022)
COVID-19 confronted many people with an abrupt shift from their usual working environ-ment to telework. This study explores which job characteristics are perceived as most crucial in this exceptional situation and how they differ from people’s previous working conditions. Additionally, we focus on job crafting as a response to this situation and how it is related to employees’ well-being. We conducted an online survey with N = 599 participants, of which 321 reported that they were telework newcomers. First, we asked participants to indicate the three most important advantages and disadvantages they see in telework. The subsequent questionnaire contained a comprehensive measure of working conditions before and during the pandemic, job crafting behaviors, and indicators of well-being. Based on the qualitative answers, we identified three major advantages and disadvantages. Quantitative results indi-cate perceived changes in all job characteristics for telework newcomers. Concerning work-ing conditions and well-being, job crafting activities that aim to increase structural and so-cial resources are important mediators. The findings underline the need to design appropriate telework conditions and encourage job crafting activities to foster occupational well-being.